Osteichthyan-like cranial conditions in an Early Devonian stem gnathostome - Giles,S; Friedman,M; Brazeau,MD (Nature, 2015)
The phylogeny of Silurian and Devonian (443–358 million years (Myr) ago) fishes remains the foremost problem in the study of the origin of modern gnathostomes (jawed vertebrates). A central question concerns the morphology of the last common ancestor of living jawed vertebrates, with competing hypotheses advancing either a chondrichthyan-1,2,3 or osteichthyan-like4,5 model. Here we present Janusiscus schultzei gen. et sp. nov., an Early Devonian (approximately 415 Myr ago) gnathostome from Siberia previously interpreted as a ray-finned fish6, which provides important new information about cranial anatomy near the last common ancestor of chondrichthyans and osteichthyans. The skull roof of Janusiscus resembles that of early osteichthyans, with large plates bearing vermiform ridges and partially enclosed sensory canals. High-resolution computed tomography (CT) reveals a braincase bearing characters typically associated with either chondrichthyans (large hypophyseal opening accommodating the internal carotid arteries) or osteichthyans (facial nerve exiting through jugular canal, endolymphatic ducts exiting posterior to the skull roof) but lacking a ventral cranial fissure, the presence of which is considered a derived feature of crown gnathostomes7,8. A conjunction of well-developed cranial processes in Janusiscus helps unify the comparative anatomy of early jawed vertebrate neurocrania, clarifying primary homologies in ‘placoderms’, osteichthyans and chondrichthyans. Phylogenetic analysis further supports the chondrichthyan affinities of ‘acanthodians’, and places Janusiscus and the enigmatic Ramirosuarezia9 in a polytomy with crown gnathostomes. The close correspondence between the skull roof of Janusiscus and that of osteichthyans suggests that an extensive dermal skeleton was present in the last common ancestor of jawed vertebrates4, but ambiguities arise from uncertainties in the anatomy of Ramirosuarezia. The unexpected contrast betw